2020
DOI: 10.1071/sh19209
|View full text |Cite
|
Sign up to set email alerts
|

International students' views on sexual health: a qualitative study at an Australian university

Abstract: Background The number of international students at Australian universities is rapidly increasing, and they contribute significantly to Australia’s economy. However, concerns have been raised for the health and wellbeing of international students, and there is limited information concerning international students with regard to their sexual health. Methods: Overall, 13 individual semi-structured in-depth interviews were conducted with 13 international students at an Australian university, aiming to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 12 publications
(18 reference statements)
0
31
0
Order By: Relevance
“…Thus, there is a need to provide sexual health programmes that are tailored to the specific needs of this population. Such programmes will be impactful if they are evidence-based and evidence around sexual health of international students in Australia is still evolving [19][20][21][22][23]. The present study adds to this emerging body of evidence.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, there is a need to provide sexual health programmes that are tailored to the specific needs of this population. Such programmes will be impactful if they are evidence-based and evidence around sexual health of international students in Australia is still evolving [19][20][21][22][23]. The present study adds to this emerging body of evidence.…”
Section: Introductionmentioning
confidence: 77%
“…44 Language and unfamiliarity with the Chinese healthcare system may create barriers to seeking healthcare for international students. 45 In addition, fearing stigma or lack of confidentiality are great barriers for international students to seek HIV and sexual health services. 46 Fear of being seen by peers and perceived shame in sexual healthcare centres might hinder students from accessing them.…”
Section: Discussionmentioning
confidence: 99%
“…These include self-perception of not being at risk of acquiring HIV, concerns over the side-effects of PrEP and the general lack of awareness of PrEP as an HIV prevention strategy (1,6,11,14). Among Australia's ethnic and migrant communities, additional intersecting factors that contribute to PrEP hesitancy include cultural taboos around sex and sexuality that play a part in the hesitancy to engage in HIV awareness and prevention, lack of awareness about PrEP due to lack of resources available in languages other than English, as well as unfamiliarity with the Australian healthcare system and stigmatizing attitudes toward PrEP users as sexually promiscuous therefore going against the cultural norm of monogamy (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Among ethnic and migrant GBMSM, including international students, studies have found that GBMSM participants were willing but did not use PrEP, in part because of the high cost of unsubsidized PrEP (1,13,18,19). For international students specifically, limited hours permitted for paid employment up to 40 h per fortnight (20), and with the Australian minimum wage of around AU$20 per hour (or US$15 per hour) before tax (21), the hesitancy to take PrEP could intersect with income level and work restrictions.…”
Section: Introductionmentioning
confidence: 99%